Sophistic criticisms of the rule of law: a comparison of Callicles and Thrasymachus - Knoll, Manuel (Filosoﬁcký časopis, 2021)
This article discusses different interpretations of Callicles and Thrasymachus’ positions. There are good reasons for interpreting Callicles as a critic of democracy and as an aristocratic political thinker whose political views are closer to Plato’s than is usually assumed. The paper argues that Callicles defends a natural right of the best citizens to rule over the crowd. However, in contrast to Plato, for Callicles the rule of the best should not aim at the common good but at their personal advantage. The paper also discusses the view that Thrasymachus is just a sociologist of power who diagnoses what actually happens in politics (Henning Ottmann, Max Salomon). This interpretation is still current, and enables us to understand important aspects of legislation in contemporary democracies. Finally, the paper argues that there are reasons to understand Thrasymachus not only as a political realist, but, similar to Protagoras, as a moral sceptic.